2012
DOI: 10.1038/onc.2012.55
|View full text |Cite
|
Sign up to set email alerts
|

MiR-130a, miR-203 and miR-205 jointly repress key oncogenic pathways and are downregulated in prostate carcinoma

Abstract: With ∼30 000 deaths annually in the United States, prostate cancer (PCa) is a major oncologic disease. Here we show that the microRNAs miR-130a, miR-203 and miR-205 jointly interfere with the two major oncogenic pathways in prostate carcinoma and are downregulated in cancer tissue. Using transcriptomics we show that the microRNAs repress several gene products known to be overexpressed in this cancer. Argonaute 2 (AGO2) co-immunoprecipitation, reporter assays and western blot analysis demonstrate that the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
150
3
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(176 citation statements)
references
References 51 publications
21
150
3
2
Order By: Relevance
“…1B). A strong downregulation of miR-205 in prostate carcinoma was also observed by Boll and colleagues (17). We again noted reduced levels of miRNAs like miR-143, miR-145, miR-320a, or miR-424 as previously described (5).…”
Section: Mirna Profiling Of Normal Prostate Tissues and Prostate Carcsupporting
confidence: 61%
“…1B). A strong downregulation of miR-205 in prostate carcinoma was also observed by Boll and colleagues (17). We again noted reduced levels of miRNAs like miR-143, miR-145, miR-320a, or miR-424 as previously described (5).…”
Section: Mirna Profiling Of Normal Prostate Tissues and Prostate Carcsupporting
confidence: 61%
“…The data revealed that the expression level of miR-203 was significantly reduced in NB tissues compared with their matched adjacent normal tissues, suggesting that the aberrant downregulation of miR-203 may be involved in the development and progression of NB. In fact, deregulation of miR-203 has been demonstrated to be associated with various cancer types, including hepatocellular carcinoma, pancreatic cancer, glioma, lung cancer, cervical cancer, prostate carcinoma, melanoma, esophageal squamous cell carcinoma and colon cancer (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The present study further revealed that the overexpression of miR-203 markedly suppressed the proliferation, migration and invasion of the SK-N-SH and SH-SY5Y NB cells, similar to the effects of Sam68 downregulation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to miR-29b, the VEGF transcript is predicted to contain binding sites for multiple miRNA types (as highlighted in Fig. 2C), such as miR-145 and miR-205, the expressions of which are reduced in PCa and have been shown to regulate VEGF in other cancer types (Szczyrba et al 2010, Fan et al 2012, Yue et al 2012, Boll et al 2013. However, it remains to be determined how effectively these miRNAs repress VEGF translation in PCa.…”
Section: Post-transcriptional Regulation Of Vegf Signaling In Pcamentioning
confidence: 99%